2011
DOI: 10.1530/joe-11-0299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Na-butyrate supplementation in milk formula on plasma concentrations of GH and insulin, and on rumen papilla development in calves

Abstract: Although the growth-promoting action of sodium-butyrate (Na-butyrate) used as a feed additive has been observed in calves and pigs, the precise mechanisms involved remain to be clarified. In this study, pre-weaning calves were given milk formula (MF) supplemented with butyrate for 6 weeks to investigate its effects on postprandial changes in the plasma concentrations of metabolic hormones, and, simultaneously, on growth performance, the weight of the digestive organs and rumen papilla development. Ingestion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 45 publications
4
41
1
Order By: Relevance
“…NeoTec5g contains a specific blend of functional fatty acids that are primarily butyric, lauric, myristic, and linolenic acid. These fatty acids have been shown to have function in the immune and digestive systems and for growth in calves, and are typically in low concentrations of the diets fed to calves (Hill et al, 2009aKato et al, 2011). The MOD rate of MR was fed at 0.66 kg of DM for 49 d. The AGG rate of MR was fed for 4 d at 0.66 kg of DM, 4 d at 0.96 kg of DM, then 34 d at 1.31 kg of DM, followed by 0.66 kg of DM for the last 7 d. The MR feedings were divided into 2 equal morning and evening meals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NeoTec5g contains a specific blend of functional fatty acids that are primarily butyric, lauric, myristic, and linolenic acid. These fatty acids have been shown to have function in the immune and digestive systems and for growth in calves, and are typically in low concentrations of the diets fed to calves (Hill et al, 2009aKato et al, 2011). The MOD rate of MR was fed at 0.66 kg of DM for 49 d. The AGG rate of MR was fed for 4 d at 0.66 kg of DM, 4 d at 0.96 kg of DM, then 34 d at 1.31 kg of DM, followed by 0.66 kg of DM for the last 7 d. The MR feedings were divided into 2 equal morning and evening meals.…”
Section: Methodsmentioning
confidence: 99%
“…A balance of AA (Hill et al, 2007b(Hill et al, , 2008 and fatty acids Kato et al, 2011;Esselburn et al, 2013) have been reported to optimize growth and health of calves, and many MR in the United States lack specific fatty acids (i.e., butyric and linolenic acids) for optimum growth and health of calves. Butyric and linolenic acid are functional in the immune and digestive systems Esselburn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been related to the promotion of energy expenditure through enhanced mitochondrial expression of PGC-1␣ and uncoupling protein 1 (UCP1) (13). A recent study has shown that butyrate supplementation of milk formula given to preweaning calves improved insulin sensitivity (23).…”
mentioning
confidence: 99%
“…In principle, the direct infusion of butyrate should be able to confer the beneficial effects similar to that induced by the butyrate-producing bacteria. The supplementation of butyrate salts is found to exert a wide range of beneficial effects to pre-and post-weaning calves and piglets, including the improvement of the gut barrier function, immune system, digestibility, and growth rate (Kato et al 2011, Kotunia et al 2004. This has been performed in human adults via oral administration of butyrate tablets (Roda et al 2007, Vernia et al 2000, butyrateproducing precursors such as tributyrin (Conley et al 1998, Vanhoutvin et al 2009 or rectal enemas (Scheppach et al 1992).…”
Section: Chaptermentioning
confidence: 99%